Physical-mechanical analysis of performance pattern knitted fabrics - Shogofurov Shaxboz Shokirjon ugli; Rahmatova Sadokat Umarjonovna; Uralov Lazizbek Saidnazar ugli; Kholikov Kurbonali Madaminovich (International Journal on Human-Computing Studies, 2021)
In the article presents the results of the analysis of physical and mechanical properties of 3 variants of pattern knitted fabric. The samples were developed on a 12-class LONG-XING LXA 252 knitting machine with a flat needle with modern high capacity. Physical and mechanical properties of the obtained samples were determined experimentally on modern equipment installed in the testing laboratory of the Namangan Institute of Engineering Technology